M73. DRIVING ABILITIES IN PATIENTS WITH SCHIZOPHRENIA. (18th May 2020) - Pardeller, Silvia; Biedermann, Falko; Haibach, Maria; Holzner, Bernhard; Kemmler, Georg; Kurzthaler, Ilsemarie; Hofer, Alex
Abstract: Background: Driving ability is a relevant factor of individual autonomy for patients suffering from psychiatric diseases. The aim of this naturalistic study was to determine the driving ability of clinically stable outpatients with schizophrenia and to determine relevant parameters for possible deficits. Methods: We included 50 outpatients with schizophrenia (ICD-10) between the ages of 18 and 65 who were on stable psychopharmacological treatment for at least three months. By means of the Wiener Testsystem (Schuhfried), reaction behaviour, the ability to observe and gain overview, reaction time, certainty in decision making as well as concentration and attention were tested. Symptomatology and extrapyramidal motor symptoms (EPS) were investigated by using the Positive and Negative Syndrome Scale (PANSS) and the Modified Simpson Angus Scale (MSAS), respectively. Results: The mean PANSS score of 55.3 ± 16.2 indicated that patients were merely mildly ill at the time of study inclusion. 48% had a MSAS score ≥3. 44% had adequate driving-specific abilities. 20% showed slight psychomotor impairments, and 36 % were considered as unfit to drive. 41.1% of the patients with a valid driver's license were not able to drive. There was a strong correlation between EPS and driving ability, while residual symptomatology was not relevant in this context. Discussion: Personal mobility is an important aspect of quality of life in people with schizophrenia. Possible danger for the general public may be conflicting with this point of view. Our investigation suggests that EPS have a major influence on the ability to drive. The missing correlation between residual symptomatology and driving abilities, on the other hand, may be explained by low mean PANSS scores. Further studies with larger sample sizes are urgently needed to address this issue.